Prevalence and Risk Factors Associated with HIV Infection among Pregnant Antenatal Care Attendees in Limpopo Province, South Africa - Boshomane, Itumeleng Tebele; Tshabalala, Kontswi Donald; Mokoena, Oratilwe Penwell; Ntuli, Thembelihle Sam (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Early screening for HIV infection provides an opportunity for mother-to-child transmission and optimizes the care of HIV-infected mothers and unborn babies to improve clinical outcomes. This study aimed to determine the prevalence and the risk factors associated with HIV infection among pregnant women attending antenatal care at the District Hospital and its feeder community health center of the Limpopo Province (LP), South Africa. The study was a cross-sectional descriptive study carried out over 2-months from 01 May 2019 to 30 June 2019. A consecutive sample of pregnant women who attended antenatal care during the study period was asked to participate. In total, 211 pregnant women participated in this study. Their mean age was 28.4±5.7 years, ranging from 18 to 41 years. More than half (56.4%) were aged <30 years old, 51.7% had secondary education, 71.1% were unmarried, and 72.0% were unemployed. The majority (66.4%) of pregnant women had multiple pregnancies and 70.6% were in the third trimester. Few (0.95%, n=2) had a history of alcohol use. The HIV prevalence was 15.2%, and significantly high in illiterate, elementary school-educated and multiparous women. The HIV infection rate in this setting is relatively associated with the level of education and parity. The social risk factors of health in each municipality should be considered when local health authorities implement policies. Women should be continually provided with health education about modes of transmission of HIV prevention particularly those with lower levels of education and reproductive age.